Acne: current perspective - Kamra, Manju; Diwan, Anupama (Creative Pharma Assent, 2017)
Acne vulgaris or acne is a multi factorial chronic inflammatory disease of pilosebaceous unit. Globally it affects approximately 9.4% of the population. It is characterized by blackheads and white heads, pinheads, large papules which may lead to scarring. Other than scarring, its main effects are psychological, such as distress and reduced self-esteem. Up to 80% of teenage girls and 90% of teenage boys are afflicted with acne. Adult acne, although less common than adolescent acne, is a significant problem for 3% to 6% of adult men and 5% to 12% of adult women. It is the most common chronic skin disorders which require urgent attention. Successful treatment of acne requires careful selection of anti-acne agents.